Structural Data, Linear and Nonlinear Optical Properties of Some Cyclic Phosphazenes: A Theoretical Investigation - Hadji, D.; Rahmouni, A. (Journal of Applied Solution Chemistry and Modeling, 2015)
We report ab initio and DFT calculation of structural data, dipole moment, diagonal vibrational and electronic contributions to polarizability, vibrational and electronic contributions to first hyperpolarizability of some cyclic phosphazenes. The electronic structure of substituted cyclic phosphazenes has been investigated using Hartree-Fock and density functional theory. The vibrational and electronic contributions to polarizabilities and first hyperpolarizability of these molecules were calculated with HF method, and different DFT levels used the traditional B3LYP and PBE functional and the long-range corrected functional like Coulomb-attenuating method CAM-B3LYP, LC-BLYP and wB97XD used different basis sets. These cyclic phosphazenes adopts a planar structure. The study reveals that the cyclic phosphazenes derivatives have large vibrational contribution to static first hyperpolarizability values. The results obtained from this work will provide into the electronic properties of this important class of inorganic polymers.